Long-Term Dynamic in Nutrients, Chlorophyll a, and Water Quality Parameters in a Coastal Lagoon During a Process of Eutrophication for Decades, a Sudden Break and a Relatively Rapid Recovery - Pérez-Ruzafa, Angel; Campillo, Sara; Fernández-Palacios, José María; García-Lacunza, Antonio; García-Oliva, Miriam; Ibañez, Helena; Navarro-Martínez, Pedro C.; Pérez-Marcos, María; Pérez-Ruzafa, Isabel M.; Quispe-Becerra, Jhoni Ismael; Sala-Mirete, Antonio; Sánchez, Olga; et al. (Frontiers in Marine Science, 2019)
Coastal lagoons are among the marine habitats with the highest biological productivity, and supports a great variety of human activities and pressures that makes them especially vulnerable to trophic imbalances. While dystrophic crises are common in many lagoons, others like the Mar Menor show homeostatic mechanisms, high resilience and clear waters. This paper analyses the water column descriptors dynamic during the last 22 years in this lagoon, in the context of a eutrophication process produced by an increase in nutrient inputs, mainly derived from agriculture. Despite the increase in nitrate loads, the lagoon maintained two decades of homeostatic regulation, keeping the water transparency and relatively low levels of nutrients and chlorophyll a (Prebreak phase), followed by a sudden change of state in 2016 with an abrupt increase in nutrients and chlorophyll a concentration and loss of water transparency (Break phase), and a relatively rapid recovery after the reduction of nutrient discharges (Recovery phase). The activation of the regulation mechanisms is manifested by an ammonium production, as a consequence of the trophic web activity. The low relationship between chlorophyll and nutrients, mainly at small spatio-temporal scales, disagrees with the eutrophication traditional models, suggesting a rapid response of primary producers to nutrient inputs and a zooplankton control in the short-term, which in turn is controlled by the rest of the trophic web components. Homeostatic properties that provide resistance to the Mar Menor lagoon to deal with eutrophication are based on several mechanisms: channelling its production towards the benthic system (maintaining high biomasses of primary producers, filter feeders and detritivores), a top-down control of the pelagic trophic web exerted by ichthyoplankton and jellyfish, and exporting surplus production outside the system. Resilience of the system would be based on the high turnover in the species composition related to the restricted connectivity with the sea, the spatio-temporal variability of the environmental conditions, and the multiplicity of spatial-temporal scales involved in lagoon processes. TRIX index was sensitive to the water quality changes. However, in our study, its current score does not allow to anticipate or alert the eutrophication risk and the trophic breakpoint of the system.